Continuous optical chlorophyll-a and turbidity data along RV SONNE cruise SO306 - Julia Oelker; Dierk Hebbeln; Claudia Wienberg (PANGAEA, 2025)
Underway optical chlorophyll-a and turbidity data were collected along the cruise track with Sea-Bird Scientific ECO FLNTU sensors installed within two autonomous measurement systems, called self-cleaning monitoring boxes (SMBs). The SMBs measure alternatingly. While one box is measuring, the other one is being cleaned. The boxes switched generally every 12 hours. The water inlet for the SMBs is at about 4 m below sea surface. Observed chlorophyll-a and turbidity data were both quality controlled. Analysis of the chlorophyll-a and turbidity data during parallel operation of the sensors in the two boxes showed significant differences between the sensors. The sensors were aligned resulting in consistent chlorophyll-a and turbidity time series. A comparison for the corrected chlorophyll-a with satellite data using the GlobColour CHL1 product was analyzed. Turbidity data were also compared to the GlobColour SPM-OC5 product. Details on all quality control steps and the comparison with satellite data can be found in the data processing report. Comparison between satellite and SMB showed moderately high agreement for the GlobColour CHL1 product with a slope close to 1. The SMB Chla data therefore seem adequate to use as a rough estimate of the Chla concentration during the expedition. Nonetheless, note that the instruments are factory-calibrated, however, no post-calibration was performed due to missing reference data. Absolute values should be challenged. Additionally, the data set user should keep in mind that some parts of the time series might be affected by non-photochemical quenching, see data processing report. It was out of the scope of the quality control to flag or correct non-photochemical quenching. The resulting data set contains the original data and corresponding quality flags achieved by the quality control algorithm as well as the corrected chlorophyll-a and turbidity data with corresponding quality flags. The data source is given through the name of the active SMB. The data set contains data during transit time and station work. We recommend to use ship extquotesingles speed to filter for only transit data.